The isolation and molecular characterization of Mycobacterium avium subsp. paratuberculosis in Shandong province, China. Issue 1 (December 2016) - Yue, Ruichao; Liu, Chunfa; Barrow, Paul; Liu, Fei; Cui, Yongyong; Yang, Lifeng; Zhao, Deming; Zhou, Xiangmei
Abstract Background Mycobacterium avium subspeciesparatuberculosis (Map) causes Johne's disease in domestic and wild ruminants. It has been a debate that whether Map can cause Crohn's disease in human. To our knowledge there is no report about molecular characterization of Map in China, although several Map strains have been reported in other country. The objectives of this study was to know the recent prevalence of Johne's disease in dairy farms in Shandong province, and have a better understanding of genotypic distribution of Map in China. Methods Johne's disease was detected from 1038 individuals in 19 dairy farms by ELISA. Map in fecal and milk specimens was identified by Ziehl-Neelsen staining and confirmed using PCR-REA. In addition, frozen sections of ileum and mesenteric lymph nodes from two Map shedding cows were performed to observe the histopathological changes. Next-generation sequencing technology was performed to get whole genome sequences. Result A total of 121 (11.7 %) animals were positive for Map antibody from 1038 sera tested, and 11 (57.9 %) dairy herds were positive for Map antibody. Typically histopathologic changes were observed in mesenteric lymph nodes. We have successfully isolated two Map strains, which both were Map-C. The current genome-wide analysis showed that the genome size of our isolates are respectively 4, 750, 273 and 4, 727, 050 bp with a same G + C content of 69.3 %, and the numbers of single nucleotide polymorphisms (SNPs) against Map K-10 are respectively 292 and 296. Conclusion Map is a prevalent pathogen among dairy cattle in China. This study successfully isolated two Map strains from one Chinese dairy herd with signs of diarrhoea, and identified that the two isolates were both Map-C. Furthermore, these isolates were most closely related to Map K-10.